ANAK PADA KELUARGA PETANI KELAPA SAWIT (DI DESA SUNGAI SIPUT KECAMATAN SIAK KECIL KABUPATEN BENGKALIS) - Istiqomah, Eni; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Globalization affected the fertility level of a family. Demand of children in a family is getting a little, faund in many communities only have 2 to 3 children only. The small number of children in the family not only can we see the family in urban but also in families residing in rural areas. It is certainly happening because of certain reason from parent. How parent interpret their childrens attendence and the consequence that will be receive after having a child becomes a parent consideration in determining the numbe of children who will be possessed. Therefore this study was conducted in order to determine the value of children in the family oil palm growers, number of children, and the expectations of parent of children in the family. To answer the questions of the study, researchers use childrens theory of value put forward by David Lucas. Subject of this study were parent who worked as a farmers in the village Sungai Siput Kecamtan Siak Kecil Kabupaten Bengkalis. The study uses data obtained through interviews, observation, ang documentation. Later and though using qualitative methods. Disclosed in accordance with the narrative of the subject ang the actual conditions in the field.Value of a child is a parent perspective to the presence of children in the family, then the perspective of parent of children will affect the desired number of children parents. Farther expectation of parent of child who had. Field finding indicate that parent decide to have a number of children two to three only. Costs incurred for the needs of children parent pretty much. Especially to meet the education, whereas children are not able to support their families. It can be concluded that parents today are more concerned with quality than quantity of children.Keyword: value of children, number of children, parental expectations.